Meningkatkan Pemahaman Siswa tentang Kedudukan dan Peran Anggota Keluarga dengan Menerapkan Metode Role Playing dan Diskusi Kelompok - Sunarsih; Ria Kurniasari (Jurnal Edukasi Sebelas April, 2020)
Learning research about the position and role of family members in class II SDN Pande, Ujungjaya District, Sumedang Regency, is based on student learning outcomes that are not in accordance with the expectations set, namely students who complete learning only reach 50%. Efforts are being made to overcome this problem by applying the role-playing method and group discussion. The formulation of the problem in this study is "How to increase the understanding of second-grade students at SDN Pande, Ujungjaya District about the position and role of family members through the application of role-playing methods and group discussions?". This study uses a Classroom Action Research design with 2 cycles starting from the stages of planning, implementing the action, observing, reflecting, and planning again. In this study, data processing is carried out in stages, firstly by selecting and grouping, secondly by describing or describing the data, and finally by concluding or giving meaning. The results obtained from this study are an increase in the average value, in the pre-cycle, it was obtained 64.3 and after the second cycle of action, it increased to 80.7. The pass percentage before the action was taken was 50%, i.e. 7 out of 14 students, while after the second cycle of action was taken, it was 86%, namely 12 out of 14 students. So the increase in the passing percentage is 36%. Thus, the application of the role-playing method and group discussion has been able to increase students' understanding in social studies learning about the position and role of family members.